Analisis Peran Bimbingan dan Konseling dalam Projek Penguatan Profil Pelajar Pancasila - Linawati Linawati; Dewi Rosanthi; Siswo Wardoyo; Anantia Aliva Rizqa; Destiani Destiani; Nabela Amelia; Sabila Asma Rizkia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study discusses the importance of integrating Guidance and Counseling (BK) in the Strengthening of Pancasila Student Profile (P5) Project at SMKN 1 Cilegon, as well as the factors that hinder the involvement of BK in this activity. P5 aims to internalize the values of Pancasila in students through a project-based approach, with a focus on character development and soft skills. However, the implementation of P5 at SMKN 1 Cilegon has not optimally involved BK. This research uses a descriptive qualitative approach to analyze the factors that cause BK's lack of participation in P5, its impact on students' social-emotional development, and a comparison with practices at other schools that have successfully integrated BK into P5. The results of the study show that administrative barriers, a lack of understanding of the role of BK, and limited communication between teachers and school management are the main obstacles. The impact of BK's non-involvement includes a reduction in the effectiveness of P5 in supporting character education and diminishing students' ability to face social-emotional challenges. This study recommends enhancing administrative support, providing training for teachers and counselors, and improving coordination among school stakeholders so that BK can optimally contribute to achieving the goals of P5. Effective integration of BK is expected to support the holistic development of students in line with the values of Pancasila.